(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
This article provides information on the economic content of investment activities, its role as an important factor in ensuring sustainable economic growth and public administration in pursuing an active investment policy, as well as investment processes in the economy of Uzbekistan.